2021
DOI: 10.3390/sym13020362
|View full text |Cite
|
Sign up to set email alerts
|

GLM-Based Flexible Monitoring Methods: An Application to Real-Time Highway Safety Surveillance

Abstract: Statistical modeling of historical crash data can provide essential insights to safety managers for proactive highway safety management. While numerous studies have contributed to the advancement from the statistical methodological front, minimal research efforts have been dedicated to real-time monitoring of highway safety situations. This study advocates the use of statistical monitoring methods for real-time highway safety surveillance using three years of crash data for rural highways in Saudi Arabia. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Accordingly, the official statistics estimated that at least 33% of all road crashes happen as vehicles alter lanes or turn off the road. Furthermore, crash data recorded from 2010 to 2017 in Middle East countries indicate that sudden lane changes produced about 17.0% of the total serious accidents, followed by speeding (12.8%) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the official statistics estimated that at least 33% of all road crashes happen as vehicles alter lanes or turn off the road. Furthermore, crash data recorded from 2010 to 2017 in Middle East countries indicate that sudden lane changes produced about 17.0% of the total serious accidents, followed by speeding (12.8%) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In prior studies, several performance metrics have been proposed to examine the power of control charts. For example, Jamal et al 39 utilized ARL and SDRL to analyse control charts formed on COM-Poisson model. Also, Kinat et al 32 and Mahmood 68 made use of run-length properties like ARL, SDRL and median run length to evaluate the Inverse Gaussian and Zero-inflated Poisson model-based schemes.…”
Section: The Simulated Poisson Modelmentioning
confidence: 99%
“…Park et al 38 studied the quantile residuals-based procedure to examine non-normal quality characteristic. Jamal et al 39 suggested EWMA and CUSUM structures originated from randomized quantile residuals and deviance residuals of COM-Poisson regression. For examining Poisson and COM-Poisson profiles, Mammadova and Özkale 40 introduced Shewhart, EWMA and CUSUM structures derived from ridge deviance residuals.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected to have the lowest EQL for the best chart. For the details on these and some other useful measures, one may be seen in studies [37][38][39][40] and the references therein. The computational algorithm for the proposed MPVC is outlined as:…”
Section: F I G U R E 1 Arl Curves Of the Proposed Charts And Their Counterpartsmentioning
confidence: 99%